Solubility Enhanced Formulation Approaches to Overcome Oral Delivery Obstacles of PROTACs - Florian Pöstges; Kevin Kayser; Jan Appelhaus; Marius Monschke; Michael Gütschow; Christian Steinebach; Karl G. Wagner (MDPI AG, 2023)
PROteolysis TArgeting Chimaeras (PROTACs) offer new opportunities in modern medicine by targeting proteins that are undruggable to classic inhibitors. However, due to their hydrophobic structure, PROTACs typically suffer from low solubility, and oral bioavailability remains challenging. At the same time, due to their investigative state, the drug supply is meager, leading to limited possibilities in terms of formulation development. Therefore, we investigated the solubility enhancement employing mini-scale formulations of amorphous solid dispersions (ASDs) and liquisolid formulations of the prototypic PROTAC ARCC-4. Based on preliminary supersaturation testing, HPMCAS (L Grade) and Eudragit® L 100-55 (EL 100-55) were demonstrated to be suitable polymers for supersaturation stabilization of ARCC-4. These two polymers were selected for preparing ASDs via vacuum compression molding (VCM), using drug loads of 10 and 20%, respectively. The ASDs were subsequently characterized with respect to their solid state via differential scanning calorimetry (DSC). Non-sink dissolution testing revealed that the physical mixtures (PMs) did not improve dissolution. At the same time, all ASDs enabled pronounced supersaturation of ARCC-4 without precipitation for the entire dissolution period. In contrast, liquisolid formulations failed in increasing ARCC-4 solubility. Hence, we demonstrated that ASD formation is a promising principle to overcome the low solubility of PROTACs.